Proposing and Testing an Intellectual Capital‐Based View of the Firm - Reed, Kira Kristal; Lubatkin, Michael; Srinivasan, Narasimhan (Journal of Management Studies, 2006)
abstract This study examines one specific aspect of the resource‐based view, intellectual capital, and its three knowledge components – human, organizational, and social capital. We hypothesize that the impact of each component on financial performance is contingent upon the values of the other components, and that these leveraging effects are themselves contingent upon the industry conditions in which a business operates. Our hypotheses are supported using line‐of‐business survey and FDIC data (within‐industry/within‐geographic region) from two non‐competing resource niches of the banking industry (personal and commercial banking).